Analysis ANALISIS KANDUNGAN RHODAMIN B PADA SAOS TOMAT DI MAKANAN JAJANAN BAKSO ACI - Nasrudin Abdul Udy (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2023)
Abstrak Analysis of Rhodamine B Content On the Tomato Sauce At Snack Food Bakso Aci Nasrudin Abdul Universitas Khairun, nasrudin.abdul91@gmail.com School-Age Children Are Nation's Investment Because They Are The Next Generation Of The Nation. Growth and development of children the optimal school age depending on the gift nutrition with quality and good and correct quantity. By consuming junk food, expected to make a donation to cover nutritional deficiency because it's for school kids Snack food is the main menu when they are at school or outside of school. Based on the background above then the formulation of the problem in this research is, there are alleged manufacturers use dangerous food additives like borax and formaldehyde on bakso aci snacks circulating around the elementary school in the District of South Ternate. Further research is needed to be certain, Are Bakso Aci snacks circulating in elementary schools District of South Ternate contain this hazardous substance. Based on the research results described in chapter IV it can be known that of all the samples of tomato sauce on bakso aci which are sold in elementary schools in the South Ternate District after being tested none of the tomato sauce tested positive for rhodamine B. These results were obtained after reacting the solution test kit Rhodamin B dissolved in 1 (one) drop of reagent A and reagent B and 4 (four) drops of reagent B2 then put in the tomato sauce. If there is a change in color red to purple then the tomato sauce contains rhodamine B. Keywords: Rodhamin B, reagent A and reagent B solutions, bakso aci, tomato sauce